Uji Efektifitas Fraksi Daun Setebal (Glochidion superbum) terhadap Penyembuhan Luka Sayat pada Mencit Putih Jantan (Mus musculus L.) - Rivelino William Putra Nazara; Habibie Deswilyaz Ghiffari; Ghalib Syukrillah Syahputra; Desy Gusmali Maniarti; Roza Erda (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Wounds can be defined as the loss and damage of anatomical cells or skin function. Wound healing consists of coagulation, inflammation, proliferation, and remodeling stages. This study aims to determine the effectiveness of the leaf fraction of the thick (Glochidion superbum) on wound healing in male white mice (Mus musculus). This study is experimental. This study used 24 male mice that were given a 10 mm long cut wound. Fractionation was carried out using the liquid-liquid extraction method. Fractionation used 3 different types of solvents, namely methanol, ethyl acetate, and n-hexane. The results showed that the ethyl acetate fraction had a faster wound healing effectiveness than the other groups. The ethyl acetate fraction contains a phenolic compound, namely methyl gallate. Methyl gallate has an important role in wound healing. Methyl gallate has the potential to be an antibacterial, antioxidant, and anti-inflammatory. The results of the Bonferroni post-hoc statistical analysis confirmed the effectiveness of the ethyl acetate fraction in faster wound healing. The thick leaf fraction was effective in healing incisions in male white mice. The ethyl acetate fraction was more effective in accelerating incision healing.